Does America need a foreign policy? [toward a diplomacy for the 21st century] - Kissinger, Henry, 1923-; Bosco, Philip (London : Free, 2001)
Focusing his attention on such hot spots as Putin's Russia and the new China, as well as such issues as the globalized economy and the demand for humanitarian intervention, Dr. Kissinger stresses the need for a coherent foreign policy that must be built on America's permanent national interests.
Subtitle from container.
Compact discs.
Read by Philip Bosco ; with an introduction read by the author.
Keywords: United States -- Foreign relations